2020
DOI: 10.1371/journal.pone.0211173
|View full text |Cite
|
Sign up to set email alerts
|

Inferring lifestyle for Aves and Theropoda: A model based on curvatures of extant avian ungual bones

Abstract: Claws are involved in a number of behaviours including locomotion and prey capture, and as a result animals evolve claw morphologies that enable these functions. Past authors have found geometry of the keratinous sheath of the claw to correlate with mode of life for extant birds and squamates; this relationship has frequently been cited to infer lifestyles for Mesozoic theropods including Archaeopteryx. However, many fossil claws lack keratinous sheaths and thus cannot be analysed using current methods. As the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 67 publications
(119 reference statements)
5
26
0
Order By: Relevance
“…In predatory birds the cross‐sectional shape of the claw is roughly as wide as it is tall making it equally strong in all directions, a helpful feature for dealing with struggling prey items. Previous studies have found considerable overlap in the morphological characteristics of bird claws assigned to predatory and perching categories (Birn‐Jeffery et al, 2012; Cobb & Sellers, 2020; Pike & Maitland, 2004). It seems that this overlap is due to the shared biomechanical function (i.e., grasping) between these two groups, again highlighting the need to categorize specimens by function instead of ecology or life habit.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In predatory birds the cross‐sectional shape of the claw is roughly as wide as it is tall making it equally strong in all directions, a helpful feature for dealing with struggling prey items. Previous studies have found considerable overlap in the morphological characteristics of bird claws assigned to predatory and perching categories (Birn‐Jeffery et al, 2012; Cobb & Sellers, 2020; Pike & Maitland, 2004). It seems that this overlap is due to the shared biomechanical function (i.e., grasping) between these two groups, again highlighting the need to categorize specimens by function instead of ecology or life habit.…”
Section: Discussionmentioning
confidence: 99%
“…Although claws are composite structures where both the sheath and ungual likely contribute to overall function, measurements of ungual features (except for the flexor tubercle) do not factor into our analysis. However, recent studies suggest that a significant correlation exists between sheath and ungual morphology (Hedrick et al, 2019) and that either structure by itself serves well for inferring function (Cobb & Sellers, 2020). It is acknowledged that the measurements of these metrics are affected by physical wearing of the claw, mostly at the apex.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We are aware that several other analyses have assessed arboreality in extinct animals based on pedal claw morphology. 51,52 However, these datasets are mostly composed of avian measurements. As bipeds and quadrupeds are known to have very different biomechanical constraints, 53 studying pterosaurs using these datasets may lead to flawed interpretations.…”
Section: Principal Coordinate Analysismentioning
confidence: 99%